2017
DOI: 10.1016/j.jcrc.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vasoactive drugs on mortality in patients with severe sepsis and septic shock. A network meta-analysis of randomized trials

Abstract: Among several regimens for pharmacological cardiovascular support in septic patients, regimens based on inodilators have the highest probability of improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 87 publications
(111 reference statements)
1
27
0
6
Order By: Relevance
“…167 'Decatecholaminisation' of the medical armamentarium is a developing line of practice in the management of critically ill patients. [168][169][170][171][172][173][174][175][176] As an established non-adrenergic vasoactive agent that offers positive cardiovascular effects (e.g. ventriculoarterial recoupling, decongestion), as well as potentially advantageous ancillary effects on kidney function and cellular-protective actions, levosimendan is both a therapeutic resource and experimental tool for investigating this new approach.…”
Section: The Next 20 Years Of Levosimendanmentioning
confidence: 99%
“…167 'Decatecholaminisation' of the medical armamentarium is a developing line of practice in the management of critically ill patients. [168][169][170][171][172][173][174][175][176] As an established non-adrenergic vasoactive agent that offers positive cardiovascular effects (e.g. ventriculoarterial recoupling, decongestion), as well as potentially advantageous ancillary effects on kidney function and cellular-protective actions, levosimendan is both a therapeutic resource and experimental tool for investigating this new approach.…”
Section: The Next 20 Years Of Levosimendanmentioning
confidence: 99%
“…Inotropic support is endorsed for restoration of an adequate cardiac output and peripheral oxygen delivery. 48 In the absence of a fully evidence-based alternative, dobutamine remains the suggested first-line inotrope for those goals, despite the observations that: (1) high levels of circulating catecholamines and adrenergic overstimulation contribute to the pathophysiology of SCM 54,76 ; (2) the adrenergic response at the cardiomyocyte level is attenuated by downregulation of β-adrenergic receptors 77,78 ; (3) adrenergic drugs have been associated with worse outcomes in a pooled network meta-analysis 36 ; and (4) esmolol, a β 1 -receptor antagonist, seems to improve the outcome of severe SCM, 78 especially in cases of persistent tachycardia. 79…”
Section: Levosimendan In Septic Shockmentioning
confidence: 99%
“…In these trials, the frequency of dobutamine use was significantly higher in the EGDT group than in the standard care group (ProCESS trial 8.0 vs. 1.1%, respectively; p < 0.001; ProMISe trial 8.0 vs. 1.1%, respectively; p < 0.001; and ARISE trial 15.4 vs. 2.6%, respectively; p < 0.0001), but there were no significant differences in the mortality between the groups. Although recent meta-analysis of randomized trials suggested inodilators such as levosimendan and dobutamine might improve the survival in septic patients [ 6 ], most studies comparing inotropes included in this study were small single center studies, and we have to be careful to interpret the results. Furthermore, the biggest randomized controlled trial showed no benefit of levosimendan in mortality or prevention for organ dysfunction in septic patients [ 7 ].…”
Section: Manuscriptmentioning
confidence: 99%